Pengaruh Literasi Keuangan, Financial Technology, dan Modal Minimal Investasi Terhadap Keputusan Investasi dengan Overconvidence Sebagai Variabel Moderasi (Studi Kasus Mahasiswa Akuntansi Wilayah Eks Karesidenan Pekalongan) - Maida Beryl Lituhayu; Raharjo, Teguh Budi; Mubarok, Abdullah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of financial literacy, financial technology, and minimum investment capital on investment decisions, with overconfidence moderating these effects. This study employs a quantitative research method with 350 respondents, analyzed using SPSS. The results indicate that financial literacy and minimum investment capital have a positive effect on investment decisions, while financial technology has no effect on investment decisions, and overconfidence does not moderate the effects of financial literacy, financial technology, and minimum investment capital on investment decisions. Keywords: Financial Literacy; Financial Technology; Minimum Invests Amount; Overconfidence; Investment Decisions